METHOD ENCODING VIDEO FRAMES BASED ON STRUCTURAL AND STATISTICAL PROPERTIES - Barannik, Vladimir; Babenko, Yurii; Barannik, Valeriy; Elіseev Evgenіy; Semenchenko, Oleksandr (Science-based technologies, 2023)
The article shows the tendency towards widespread use of remote video information support in various applied areas. It is proved that the key factor in determining this approach to the collection and exchange of video resources is martial law in the state. On the basis of system analysis, a set of requirements for the qualitative characteristics of video information support is established. At the same time, it is shown that such requirements entail a powerful increase in the bit load intensity on data networks. Consequently, under the conditions of organizing the transmission of information on the basis of wireless communication channels in difficult conditions regarding interference conditions, an information and technological imbalance arises. Accordingly, this indicates the existence of scientific and applied problems. It concerns improving the characteristics of video information resources by categories of availability and integrity in the context of the use of remote infocommunication technologies for collecting and processing video data. It is substantiated that load reduction on infocommunication networks is achieved on the basis of application of methods to reduce the volume of video data. However, in the process of creating such technologies, they stumble with certain problematic facts. Therefore, it is necessary to create further development of technological approaches to encoding video data in the direction of resolving the contradiction between different categories of information security. To build a new method, it is proposed to use one of the standardized technologies as the base platform. The main stages of development of the method of differentiated coding of video resources to ensure their integrity and accessibility, taking into account the level of structural and statistical saturation of segments, are outlined. The method of differentiated coding of segments based on structural-statistical saturation is developed. Differential processing of video frame segments is carried out taking into account their previous typing, depending on significance from the position of preserving the semantic integrity of video resources.Keywords: video frame segments, video information security, video data compression, semantic integrity of video frames.